TAFSIR ILMI: Ilmu Pengetahuan sebagai Sumber Tafsir dengan Pendekatan Eklektik - Ulum, Khoirul (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2020)
In the knowledge of the Qur'an there are two ways to understand the Qur'an, namely tafsir and ta'wil. Until now, the use of the term tafsir in the country may even be more popular throughout the Islamic world than ta'wil. Tafsir is known as a way to parse the language, context and moral messages contained in the text or scripture. The text is categorized as an interpretive paradigm that uses a bayani epistemology. Meanwhile, ta'wil is a way to understand the text by making the text and or more accurately called the understanding, meaning and interpretation of the text as an "object of study". In the conventional tradition of Islamic studies, this new tradition of making texts as "objects" is less well known, because of the assumption from the prevailing Islamic studies that the ulum al-Qur'an is "mature and standard". One of the things that has been standardized is what is called ta'wil batini, which is somewhat equivalent to the tafsir al-isyari. The ta'wil al-Ilmi approach seeks to make the text or more precisely the understanding of individuals, groups of mazhab, sect, organization, culture of the text as the object of new Islamic study. Tafsir al-Ilmi utilizes a hermeneutical approach to Islamic intellectual treasures, both classical, modern and contemporary. This article will discuss the existence of scientific interpretations that try to relating the theological content of the Qur’an with scientific premises.. Keywords : saintific exegesis, ta’wil and tafsir